Structure of the Millen Schist Belt (Antarctica): Clues for the tectonics of northern Victoria Land along the paleo‐Pacific margin of Gondwana. Issue 4 (11th April 2014) - Crispini, Laura; Federico, Laura; Capponi, Giovanni
Abstract Northern Victoria Land (Antarctica) belonged to the active proto‐Pacific margin of Gondwana, which was the site of convergence during the Paleozoic. This study provides new insights into the structural architecture of northern Victoria Land, focusing on the boundary area between the Bowers and Robertson Bay terranes, i.e., in the Millen Schist Belt. It is a high‐strain equivalent of the adjoining terranes, presently delimited by the Leap Year and the Handler faults. Our study reveals that these two faults overprint a preexisting transitional deformational boundary and are associated with a significant syntectonic circulation of fluids and mineralization. The Millen Schist Belt consists of two lithotectonic packages, juxtaposed along the Crosscut‐Aorangi duplex thrust system, related to late Ross deformation. As there is increasing evidence of a post‐Ross contractional event in northern Victoria Land, we suggest that the structural architecture of the Bowers‐Robertson Bay terrane boundary results from a long‐lasting SW‐NE contractional regime, during the Ross‐Delamerian Orogeny and still active afterward. This points to an extension of the Australian Lachlan Orogeny in Antarctica. The similarity of the structural architecture, the gold mineralization, the rock type, and the age supports the correlation of the Bowers and the Robertson Bay terranes with the Stawell Zone of the Lachlan Fold Belt. In our new tectonic scenario the Lanterman Fault (northern Victoria Land) plays the same role as the Moyston Fault (southeastern Australia), and the Leap Year and Handler faults correlate with the "intra‐zone faults" of the Stawell Zone (e.g., the Ararat‐Stawell Fault Zone).